PHYSICAL DEVELOPMENT OF PRESCHOOL CHILDREN IN ORGANIZED GROUPS (European Journal of Interdisciplinary Research and Development, 2024)
The purpose of the study is to study the physical development and morbidity of preschool children and to conduct a hygienic assessment. Research materials and methods: 502 children educated in a preschool educational institution underwent a medical examination, and a hygienic assessment of their physical development was performed using the generally accepted method. Results: The results of a comprehensive assessment of physical development showed that 76% of children had an average level of physical development, 8% had above-average physical development, 2% had high physical development, 8% had below-average physical development, and 6% had very low physical development. 82% of children had harmonious physical development, and up to 28% had certain changes in somatometric indicators. The results of the assessment of children's health indicators showed that 83% of preschool children needed to be healthy.